Acoustic-linguistic intervention model in the rehabilitation of children and adults with central auditory processing disorder - Arista Rangel, Juliana; Reyes Pérez, Gloria; Cisneros Chico, Jesús Emmanuel; Lino-González, Ana Luisa (Revista de Investigación en Logopedia, 2026)
Central auditory processing disorder is characterized by difficulty interpreting acoustic signals, generating problems in efficiently and effectively processing auditory information through the skills of attending, discriminating, recognizing and understanding. This study aims to evaluate the impact of the acoustic-linguistic intervention model in the rehabilitation of patients with central auditory processing disorder. In this retrospective, descriptive and comparative study, 36 records of patients diagnosed with central auditory processing disorder who received six months of therapy between 2013 and 2023 were reviewed. Descriptive analysis was performed (mean, standard deviation, percentage and frequency), to determine the difference between groups, Chi-square and Wilcoxon were calculated to determine the difference in the performance of the pre- and post-intervention psychoacoustic tests with a significance of p
Keywords: Acoustic-linguistic intervention model; Central auditory processing disorder; Psychoacoustic tests; Rehabilitation; Therapy